African theology in the intellectual journey of Alioune Diop - (:unkn) unknown (My University, 2014)
The African theology emerged from the inability of the missionary theologies in Africa in the 19th and 20th centuries, to address the challenges of the complex African reality. Indeed, the evangelization of Africa was sustained by theologies based on the salvation of souls and implantation, which were only resulting from the western experience and the western view on the African way of life. The African theology emerging from the African intellectuals’ commitment aims at deconstr...
Keywords: African Research